The Influence of Income and Lifestyle on Financial Management Behavior through Financial Knowledge in BMKG Employees of Bali Province - Ni Kade Juniasih; I Gusti Ngurah Bagus Gunadi; I Made Dauh Wijana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Individual financial management is the process of planning, regulating, and controlling income and expenses so that the needs of life can be met in a balanced manner. The study aims to analyze the influence of income and lifestyle on financial management behavior through financial knowledge in BMKG employees of Bali Province. The population and sample in this study were all employees of BMKG Bali Province as many as 199 respondents who were determined using census techniques. Data collection was carried out using questionnaires, interviews and documentation. Data analysis was carried out using partial least square (PLS) analysis. The results of the analysis show that income has a positive and significant effect on financial management behavior through BMKG employees of Bali Province, that lifestyle has a negative and significant effect on financial management behavior in BMKG employees of Bali Province, financial knowledge has a positive and significant effect on financial management behavior in BMKG employees of Bali Province, income has a positive and significant effect on financial knowledge in BMKG Bali Province employees, lifestyle has a negative and significant effect on financial knowledge in BMKG Bali Province employees, income has a positive and significant effect on financial management behavior through financial knowledge in Bali Province BMKG employees and lifestyle has a negative and significant effect on financial management behavior through financial knowledge in Bali Province BMKG employees.